Ischemia as a common trigger for Alzheimer’s disease - Elman-Shina, Karin; Efrati, Shai (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease has various potential etiologies, all culminating in the accumulation of beta -amyloid derivatives and significant cognitive decline. Vascular-related pathology is one of the more frequent etiologies, especially in persons older than 65 years, as vascular risk factors are linked to both cerebrovascular disease and the development of AD. The vascular patho-mechanism includes atherosclerosis, large and small vessel arteriosclerosis, cortical and subcortical infarcts, white matter lesions, and microbleeds. These insults cause hypoperfusion, tissue ischemia, chronic inflammation, neuronal death, gliosis, cerebral atrophy, and accumulation of beta-amyloid and phosphorylated tau proteins. In preclinical studies, hyperbaric oxygen therapy has been shown to reverse brain ischemia, and thus alleviate inflammation, reverse the accumulation of beta-amyloid, induce regeneration of axonal white matter, stimulate axonal growth, promote blood–brain barrier integrity, reduce inflammatory reactions, and improve brain performance. In this perspective article we will summarize the patho-mechanisms induced by brain ischemia and their contribution to the development of AD. We will also review the potential role of interventions that aim to reverse brain ischemia, and discuss their relevance for clinical practice.